MODEL MANAJEMEN KINERJA GURU BERBASIS NILAI-NILAI ISLAM: SEBUAH STUDI LITERATUR KRITIS - Vivi Puspasari; Jamilus (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to analyze the concept of teacher performance within the framework of Islamic value-based human resource management (HRM) and to formulate a conceptual model relevant to improving the quality of education in madrasahs. This research employs a descriptive qualitative approach using library research, drawing data from books, accredited national journals, and national educational regulations. The findings reveal that teacher performance is a key determinant of educational quality, encompassing the ability to plan, implement, and evaluate learning, as well as demonstrating integrity and moral exemplarity. The integration of Islamic values ihsan, sincerity, role-modeling, and tajdid significantly strengthens teachers’ motivation, work ethic, and accountability. The proposed Islamic value-based HRM model synthesizes three fundamental foundations: Islamic normative principles, modern performance management theory, and recent empirical studies, resulting in a more holistic teacher performance assessment system. The model includes stages of performance planning, implementation, assessment and supervision, feedback and professional development, and accountability. This study contributes conceptually to the development of teacher performance governance in madrasahs and offers a practical framework for enhancing the quality of Islamic education sustainably.